2014
DOI: 10.1002/ar.23045
|View full text |Cite
|
Sign up to set email alerts
|

2‐(Pro‐1‐ynyl)‐5‐(5,6‐dihydroxypenta‐1,3‐diynyl) Thiophene Induces Apoptosis Through Reactive Oxygen Species‐Mediated JNK Activation in Human Colon Cancer SW620 Cells

Abstract: 2-(Pro-1-ynyl)25-(5,6-dihydroxypenta-1,3-diynyl) thiophene (PYDDT) is a naturally occurring thiophene isolated from the roots of Echinops grijsii, a Chinese herbal medicine used to treat colon cancer, breast cancer, and lung cancer. There are many reports on the clinical use of Echinops grijsii alone or in combination with other herbs to treat malignant tumors. We previously reported that the expression and activity of phase II enzymes including GSTs and NQO1 could be induced through the activation of Keap1-Nr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Nrf2, a redox‐sensitive transcription factor, is stimulated by the presence of electrophonic chemicals and ROS, which contribute to the translocation of Nrf2 into the nucleus where it binds to AREs and activates a series of cytoprotective genes, such as HO‐1 and NQO1. The protective properties of Nrf2 have been supported by observations of decreased genotoxic damage, reduced cell proliferation, and increased apoptosis of colon cancer cells, in addition to lower ROS levels in a carcinogen‐induced CRC mouse model . Recent studies have recognized the effect of LUT in modulating epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2, a redox‐sensitive transcription factor, is stimulated by the presence of electrophonic chemicals and ROS, which contribute to the translocation of Nrf2 into the nucleus where it binds to AREs and activates a series of cytoprotective genes, such as HO‐1 and NQO1. The protective properties of Nrf2 have been supported by observations of decreased genotoxic damage, reduced cell proliferation, and increased apoptosis of colon cancer cells, in addition to lower ROS levels in a carcinogen‐induced CRC mouse model . Recent studies have recognized the effect of LUT in modulating epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…When NRF2 activates, it exerts a cytoprotective effect by decreasing genotoxic damage and promoting autophagy [ 23 ]. Sometimes, NRF2 expression leads to reduced cell proliferation and increased apoptosis of colon cancer cells [ 24 27 ]. In all cases, the authors observed the same final result, namely reduced risk of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC), a common human malignancy, accounts for approximately 600,000 death cases annually worldwide (Sung et al, ). Recent statistics show that the incidence rate of CRC has been dramatically increasing in China, ranking only after the lung cancer and the gastric cancer (Xu et al, ; Chen et al, ). Currently, surgical resection remains the mainstream therapeutic measure for CRC (Li and Ma, ).…”
mentioning
confidence: 99%